O projeto católico antimoderno: reflexos no Brasil na obra de Alceu Amoroso Lima (1930-1940) - Loss, Bruno Zottele (2023)
The crucial objective of the present work is to investigate the intellectual Alceu Amoroso Lima’s thought within the thoughtsystem linked to the Roman Catholic ecclesiastical centralization initiated in the 19th century as a reaction to the changes brought about by the French Revolution and known as ultramontanism. It will also address the performance of the prior mentioned writer in Brazilian society in the 1930s, in which he radically assumed the traditionalist perspective. Born in 1893 to a wealthy family in Rio de Janeiro, Alceu Amoroso Lima was initially influenced by the secularism and agnosticism of the First Republic. In 1924, his correspondence with Jackson de Figueiredo begun, which led him to convert to Catholicism in 1928. After Jackson de Figueiredo's death, in the same year, at the request of Dom SebastiãoLeme, Archbishop of Rio de Janeiro, he took over the management of the Dom Vital Center and the magazine A Ordem. Alceu Amoroso Lima would cause immense influence on the Brazilian Catholic intellectuals, actively participating in the Catholic project of penetrating social institutions to instill in them the principles of Catholicism. Concerning the Church, he was elected president of the National Board of Brazilian Catholic Action in 1934, remaining in office until 1945. In addition, he played an important role in founding the Catholic Electoral League, writing its initial project and becoming its first general secretary. In 1932, he also participated in the foundation of the Catholic Coalition of Higher Studies (embryo of the current Pontifical Catholic University) and the National Confederation of Catholic Workers. The object of this research isAlceu Amoroso Lima’s thoughts in the 1930s, using the books he published during that period as a source. The chosen approach values the New Political History, in JeanFrançois Sirinelli’s perspective, who presents the history of intellectuals as an autonomous field, located at the intersection of political, social and cultural histories. The revival of political history is part of a movement back to the agent subject, breaking with socioeconomic determinism.